Slikovna citometrija v onkologiji - Strojan Fležar, Margareta (Medicinski razgledi, 2002)
Image cytometry is a static, quantitative analytical method used for objectivemeasurement of numerous cell characteristics on glass slides. Specifically, it makes it possible to measure the DNA content and the nuclear texture features of single cells, either cancerous or normal, or of single cells belonging to an undefined stage of neoplastic transformation. Monolayered single cell slides are required for optimal analysis using an image cytometer. Cell preparations are stained according to the Feulgen methodfor stoichiometric staining of DNA in the cell nucleus. An image cytometer is an optical electronic system equipped with high-powered computers. Numerous nuclear texture features are calculated from nuclear images, which are acquired via image cytometer. New image cytometric features of malignant cells could be used as additional prognostic factors, with standard clinical and histopathologic factors that are commonly used to predict the course of the disease and the patient's response to treatment. Above all, we are hoping that image cytometric analysis of subvisual changes of chromatin in normal cells will provide new tests for cancer detection at preclinical stages.
Keywords: Neoplasms; Novotvorbe; tumor; Pathology; Ploidije; Slikovna citometrija; Image Cytometry; onkologija; Ploidies; merilne metode; diagnostika